Sosialisasi dan Pembuatan Elisator Biosaka Guna Mendukung Pertanian Berkelanjutan Pada Kelompok Wanita Tani Wirajaya Sarilamak - Deliana Andam Sari; Ayu Kurnia Illahi; Yummama Karmaita; Dedeh Kurniasih; Anidarfi Anidarfi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The main problem for Indonesian farmers in cultivating horticultural and food crops is that cultivation methods are still conventional. This means that to increase plant productivity using inorganic fertilizers is more dominant than using organic fertilizers. The socialization activity for making biosaka elicitors was carried out on July 28 2023. And August 15 2023. The method of implementing the service activities at the first meeting was socialization on making biosaka elicitors. The socialization activity was carried out at the KWT Wirajaya meeting hall, this activity took the form of a discussion and briefing regarding the process of making biosaka elicitors. The next meeting was a demonstration of making the Biosaka Elisator. The aim of this community service is: Through training in making biosaka elicitors, we can educate farmers about the use of grass material available in the environment to support sustainable agriculture. The socialization and production of biosaka elicitors at KWT Wira Jaya has educated farmers about the benefits of grass material in the environment. Members of the Wira Jaya women's farmer group can make biosaka extractors to be applied to cultivated plants.paragraph, which is the essence of scientific papers.